1999
DOI: 10.1148/radiology.211.1.r99ap03147
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal and Pleural Findings in Patients with and Patients without Acute Pulmonary Embolism Detected at Spiral CT

Abstract: Parenchymal and pleural findings at CT are of limited value for differentiating patients with PE from those without PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
8
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 24 publications
9
78
8
11
Order By: Relevance
“…The advantages of CTA-rapid and widely available examinations, the ability to perform lower-extremity venous imaging concurrently if needed, the high proportion of definitive diagnostic results, and the ability of CT to provide additional diagnostic information (30,31) that may be of clinical importance-secure a place for CTA as a first-line diagnostic imaging modality in appropriately selected patients. However, the advantages of perfusion scintigraphy-lower cost, much lower radiation dose, avoidance of iodinated contrast material, and technical simplicity-can now be considered together with a contemporary characterization of the diagnostic accuracy of the test in a predominantly outpatient population.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of CTA-rapid and widely available examinations, the ability to perform lower-extremity venous imaging concurrently if needed, the high proportion of definitive diagnostic results, and the ability of CT to provide additional diagnostic information (30,31) that may be of clinical importance-secure a place for CTA as a first-line diagnostic imaging modality in appropriately selected patients. However, the advantages of perfusion scintigraphy-lower cost, much lower radiation dose, avoidance of iodinated contrast material, and technical simplicity-can now be considered together with a contemporary characterization of the diagnostic accuracy of the test in a predominantly outpatient population.…”
Section: Discussionmentioning
confidence: 99%
“…Linear (plate-like) atelectasis is also seen with increased frequency on CT in patients with acute PTE. Other findings, such as areas of decreased attenuation and pleural effusion, are not helpful in distinguishing patients with and without acute PTE (9,10) . A number of technical, anatomical, and patient related pitfalls may lead to misinterpretation of the CT images.…”
Section: Interpretation Of Imagesmentioning
confidence: 99%
“…Diagnosis of acute PTE requires assessment of both the vascular and parenchymal findings. Assessment of the lung windows is important not only to identify the pulmonary arteries by their proximity to the bronchi, but also to assess for the presence of ancillary signs that may be helpful in suggesting the presence of pulmonary embolism (9,10) . The most helpful ancillary sign is the presence of a non-enhancing pleural-based wedge-shaped pulmonary opacity (Fig.…”
Section: Interpretation Of Imagesmentioning
confidence: 99%
“…In one study, CTPA identified pleural or parenchymal abnormalities that explained indeterminate defects on V/Q scans in 57% of patients; 11 in other studies, alternative intrathoracic findings were identified in 11% to 85% of patients undergoing CTPA; 6,8,9,13,32,47-51 these additional findings were nonspecific, occurring both in patients with and without PE. 52 Although other such intrathoracic abnormalities may not imply a need for further evaluation, their identification may affect patient management.…”
Section: Ct Pulmonary Angiographymentioning
confidence: 99%